2014
DOI: 10.4103/2231-0770.127414
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with deciduous tooth decay in Iraqi preschool children

Abstract: Introduction:Tooth decay (TD) is common in children with significant consequences on systemic well-being, growth and quality of life, as well as increasing the risk of decay in the permanent teeth.Aim:The aim of the present study is to define risk factors associated with deciduous TD (DTD) in Iraqi preschool children.Materials and Methods:From the 1st June to 31st December 2012, a case-control study was carried out on 684 children under the age of 6 years who attended Al-Aulwyiah pediatric teaching hospital in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
(15 reference statements)
2
14
0
Order By: Relevance
“…There was a significantly higher statistical correlation between tooth brushing frequency and ECC (p < 0.001). This augments the notion that low frequency and improper tooth brushing methods are closely associated with ECC 17 .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…There was a significantly higher statistical correlation between tooth brushing frequency and ECC (p < 0.001). This augments the notion that low frequency and improper tooth brushing methods are closely associated with ECC 17 .…”
Section: Discussionsupporting
confidence: 60%
“…Our study showed three times higher frequency of ECC in children who did not maintain the proper oral hygiene and two times higher ECC prevalence in children who never used fluoride toothpaste as well as other fluoride supplements. On oral hygiene significance as the risk factor for ECC development was also pointed out in the research of Al-Mendalawi and Karam 17 , who emphasized that there was a significantly higher statistical correlation between tooth brushing frequency and ECC. There was a significantly higher statistical correlation between tooth brushing frequency and ECC (p < 0.001).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…6 Brushing with fluoridated toothpaste is one of the measures for caries prevention. 27 However, this preventive measure may be inadequate in young children, due to their poor dexterity. 28 Thus, brushing should be practiced or supervised by parents/caregivers until the child is able to perform it alone.…”
mentioning
confidence: 99%
“…Number of studies had been carried out for the prevalence of dental caries in preschool children, the dmft showed wide variation among different populations ranging from 1.5 in Brazil up to 11 in Kosovo. [4,[7][8][9][10][11] There is a paucity of literature available regarding prevalence of dental caries among preschool children in Sudan. Raadal et al (1993) studied caries prevalence among 4-5 years old preschool children, the mean decayed, missed, filled teeth (dmft) was 1.68 [12].…”
Section: Introductionmentioning
confidence: 99%